The effect of entrepreneurial orientation, use of information technology, and innovation capability on SMEs' competitive advantage and performance: evidence from Indonesia - Shabrina Widyanti; M Mahfudz (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2020)
The purpose of this paper is to analyze the effect of entrepreneurial orientation, the use of information technology, and the capability of innovation on competitive advantage and performance of SMEs through competitive advantage. In this research, the sample was 125 SMEs joined in the digital class